Cutting-edge cooling techniques for photovoltaic systems: a comprehensive review - Rajamony, Reji Kumar; Sridhar, K.; Kalidasan, B.; Mishra, Richa; Farade, Rizwan A.; Megalingam, A.; Raj M, John Iruthaya; Nur-E-Alam, Mohammad; Abedin, Tarek (Springer Nature, 2025)
The efficiency of photovoltaic (PV) systems is often limited due to surface temperature increases, which result from absorbed solar energy being converted into heat. This rise in temperature reduces power output, system performance, and panel lifespan. To address these challenges, combined photovoltaic thermal (PVT) systems have emerged, enabling the simultaneous generation of electricity and thermal energy. This review provides a detailed analysis of the factors affecting PV panel efficiency, explores various feasible cooling techniques including innovative methods to mitigate excessive heating, and highlights opportunities for future research in this field. The article focuses on the experimental and theoretical advancements in PV cooling over the past decade, offering valuable insights and practical guidelines for researchers aiming to improve PV module cooling strategies. Additionally, an economic assessment of PVT systems is conducted, evaluating their financial feasibility in terms of payback periods and costs. The review also presents a comparative analysis of PVT techniques, addressing their benefits, challenges, and potential applications. This work aims to serve as a comprehensive resource for researchers exploring the viability and industrial applications of PVT systems, paving the way for more efficient and sustainable solar energy solutions.